Integrating participatory data acquisition and modelling of irrigation strategies to enhance water productivity in a small-scale irrigation scheme in Tigray, Ethiopia - Habtu, S.; Erkossa, Teklu; Froebrich, J.; Tquabo, F.; Fissehaye, D.; Kidanemariam, T.; Xueliang Cai (Wiley, 2020)
Application of participatory modelling to water-saving strategies in smallholder farming is rare. Farmer-preferred and efficient strategies were identified through participatory modelling. The farmers' basin irrigation and scheduling (I), farmers' scheduling with furrow strategy (II), farmers' scheduling with alternate furrow strategy (III) and scheduling at 55% maximum allowable depletion (MAD) (IV) were evaluated for maize (Zea mais) and barley (Hordeum vulgare) using the FAO AquaCrop model. The results showed that I resulted in over-irrigation for maize and under-irrigation for barley, while IV resulted in maximum yield (8.6 t ha-1 for maize and 2 t ha-1 for barley) with maximum (1.8 kg m-3) and minimum (0.8 kg m-3) water productivity of maize under IV and I, respectively. A shift from I to IV (most preferred strategy by farmers) can save 8440 mm of water, which can possibly bring back 18.5 ha of land into irrigation. It is essential to interact with farmers on a basis of mutual comprehension to increase their trust and to lay a base for discussion, awareness raising and decision making. The transdisciplinary approach, Community of Practice (CoP) and Learning Practice Alliance (LPA) were appropriate platforms for participation. The increased crop yield and water productivity may contribute to ecological and economical sustainability and social equity.